Risk Stratification of Penicillin Allergy Labeled Children: A Cross-Sectional Study from Jordan - Alsulaiman JW; Kheirallah KA; Alrawashdeh A; Saleh T; Obeidat M; Alawneh YJ; Abu Sanad Z; Amayreh W; Alawneh RJ (Dove Medical Press, 2024)
Jomana W Alsulaiman,1 Khalid A Kheirallah,2 Ahmad Alrawashdeh,3 Tareq Saleh,4 Maha Obeidat,5 Yareen J Alawneh,2 Ziydoun Abu Sanad,5 Wajdi Amayreh,1 Rama J Alawneh2 1Department of Pediatrics, Faculty of Medicine, Yarmouk University, Irbid, Jordan; 2Department of Public Health and Family Medicine, Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan; 3Department of Allied Medical Sciences, Faculty of Applied Medical Sciences, Jordan University of Science and Technology, Irbid, Jordan; 4Department of Pharmacology and Public Health, Faculty of Medicine, The Hashemite University, Zarqa, Jordan; 5Department of Pediatrics, Princess Rahma Teaching Hospital, Irbid, JordanCorrespondence: Jomana W Alsulaiman, Associate Professor of Pediatrics, Department of Pediatrics, Faculty of Medicine, Yarmouk University, Irbid, 21163, Jordan, Tel + 962 07 9941 2277, Email jomana.a@yu.edu.joBackground: Implementing allergy testing among children with a reported history of penicillin allergy could be challenging, particularly in developing countries with limited resources. This study screened and risk-stratified the likelihood of true penicillin allergy among children labeled with penicillin allergy in Jordan.Methods: A web-based survey, completed by parents, assessed history, type, and severity of penicillin allergic reactions, including age at diagnosis, symptoms, time to the reaction, reaction's course and resolution, and received medical evaluation/testing. Low-risk allergic symptoms were defined as vomiting, diarrhea, headache, dizziness, itching, rash, cough, or runny nose without evidence of anaphylaxis or severe cutaneous reactions.Results: A total of 530 parents of "penicillin allergy"-labeled children completed the survey. Of these, 86.4% reported allergic reactions to penicillin and 13.6% reported avoidance of penicillin due to family history. Among the former, 52.2% were male, 67.3% were three years old or younger when the reported reaction was established, and 68.3% experienced exclusively low-risk symptoms. Overall, skin rash was the most reported symptom (86.0%). High-risk symptoms were reported in 31.5% of children. About two-thirds (64.0%) of children were reported to have experienced symptoms after the first exposure to penicillin. The most common indication for antibiotic use was a throat infection (63.8%). Asthma comorbidity was significantly higher among high-risk (24.8%) compared low-risk group (11.5%).Conclusion: In Jordan, many parent-reported penicillin allergic reactions seem to be clinically insignificant and unlikely to be verifiable, which can adversely affect patients' care and antimicrobial stewardship. An appropriate clinical history/evaluation is a key step in identifying true immunoglobulin E-mediated allergic reactions and risk stratifying patients for either de-labeling those with obviously non‐immune-mediated reactions or identifying candidates for direct oral challenge test.Keywords: children, drug hypersensitivity, drug resistance, Jordan, penicillin resistance